Alkali metal secondary batteries and their uses
Patent Information
- Application Number
- KR1020227001757
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-18
- Filing Date
- 2020-06-16
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2040-06-16
Smart Images

Figure 112022006230650-PCT00001_ABST
Abstract
Description
Technology Field
[0001] An alkali metal secondary battery is provided. The secondary battery comprises a cathode, an anode, and an electrolyte arranged between the cathode and the anode and having alkali metal ion-conducting contacts on carbon layers of the cathode and the anode. The anode comprises or is composed of a carbon layer, and the carbon layer alone or in combination with an electrically conductive substrate forms an electrically conductive contact. The secondary battery is characterized by including a first type of pore in which the carbon layer cannot access the electrolyte and is suitable for absorbing an alkali metal electrochemically deposited in metallic form during the charging process of the alkali metal secondary battery. The alkali metal secondary battery is characterized by very high specific capacity, high power density, high cycle stability, high long-term stability, and high operational reliability. Background Technology
[0002] Increasing the energy density of battery cells is a global research and development goal, above all, to expand the range of electric vehicles. The focus is on solid electrolytes, as solid electrolytes are expected to enable the safe and stable operation of metallic lithium anodes, thereby replacing thicker and heavier graphite anodes.
[0003] However, there are still many challenges regarding the use of lithium as an anode. The battery electrolyte has a two-dimensional interface through which ions diffuse during the charging and discharging processes. Since pores or dendritic structures do not form at the interface and thus mechanical stress is not generated in the cell, particularly in the solid electrolyte, reversible mass transport of lithium ions is possible only at low charging currents, elevated temperatures, and high pressures for the cell stack. These conditions have significantly limited the scope of application to date. This problem remains unresolved. For this reason, all-solid-state batteries have not yet been produced on an industrial scale.
[0004] It is known that all-solid-state batteries with a graphite anode can operate stably. However, the specific capacity is limited to 372 mAh / g (lithium insertion mechanism in graphite). The problem to be solved
[0005] Based on this, the objective of the present invention is to provide an alkali metal secondary battery characterized by high capacity, high power density, and high cycle stability, and by the lowest possible mechanical stress acting on the components of the secondary battery during operation, thereby improving the long-term stability and operational safety of the battery. means of solving the problem
[0006] The above objective is achieved by a lithium secondary battery having the features of claim 1 and an application according to claim 16. The dependent claim demonstrates an advantageous development.
[0007] According to the present invention, an alkali metal secondary battery comprising the following is provided, and
[0008] a) Cathode;
[0009] a) an anode comprising or composed of a carbon layer, wherein the carbon layer forms an electrically conductive contact alone or in combination with an electrically conductive substrate; and
[0010] b) an electrolyte arranged between the cathode and the anode and having alkali metal ion conductive contacts on the carbon layers of the cathode and the anode;
[0011] The carbon layer is characterized by including a first type of pore that is inaccessible to the electrolyte and suitable for absorbing alkali metal electrochemically deposited in a metallic form during the charging process of the alkali metal secondary battery.
[0012] The term “carbon layer” means a layer made of an electrically conductive carbon material selected from the group consisting particularly of porous carbon, carbon black, graphene, graphite, graphite-like carbon (GLC), carbon fibers, carbon nanofibers, carbon hollow spheres, and mixtures or combinations thereof.
[0013] Accordingly, certain desirable characteristics of the “carbon layer” (e.g., pore volume, secretion, pore size, etc.) relate to a layer composed solely of carbon. In principle, this carbon layer may include other materials (e.g., binders and / or alkali metals). For example, if the carbon layer includes additional materials (e.g., for a second type of pore), certain characteristics may fall outside the scope provided herein.
[0014] Alkali metal secondary batteries are characterized not only by very high specific capacity and high power density, but also by very low mechanical stress acting on the components of the secondary battery during operation, so alkali metal secondary batteries possess high long-term stability and high operational reliability.
[0015] One reason for the high capacity, high power density, and cycle stability is the first type of pores. The first type of pores allow for the efficient and reversible absorption of deposited metallic alkali metals. What is important in this specification is a situation where the electrolyte of the secondary battery cannot penetrate the first type of pores.
[0016] In fact, the provided alkali metal secondary battery returns to a surprising discovery: it is known that when an alkali metal secondary battery is discharged, the metallic alkali metal is oxidized into alkali metal ions by the emission of electrons. Theoretically, the alkali metal ions generated by this process can be efficiently absorbed and converted by the electrolyte only when in direct contact with the alkali metal ions. In other words, if the generated alkali metal ions lose contact with the electrolyte, the transport of the alkali metal ions to the electrolyte must be very inefficient or even cease. However, the applicant discovered, surprisingly, that this is not the case when the carbon layer described above is used. It was noted that even alkali metal ions generated within the first type of pores and far from the electrolyte are efficiently transported to the electrolyte through the carbon network (especially within the first type of pores), and charge transport does not cease as expected.
[0017] An alkali metal secondary battery may be characterized by providing a chemical modification favorable for the absorption of metallic alkali metals generated by deposition in a first type of pore. The chemical modification is preferably selected from the group consisting of a layer on the pore surface, nanoparticles on the pore surface, at least one chemical functional group on the pore surface, and combinations thereof. Additionally, the first type of pore may have a specific pore geometry and / or pore properties. The formation of a metallic structure within the first type of pore may be facilitated by the pore geometry and / or pore properties. Thus, the overpotential (energy barrier) for the separation of alkali metals from the electrolyte may be reduced. In microporous carbon (pore diameter < 2 nm), the formation of metallic Li clusters exceeding 0 V (v. Li / Li+) may be observed, which indicates a decrease in the thermodynamic enthalpy of formation.
[0018] The pores of the first type may have a pore size in the range of 0.5 to 100 nm. Additionally, the pores of the first type may have a pore size of > 2 nm. It is particularly desirable for the pores of the first type to have a pore size of < 2 nm, as metal Li cluster formation exceeding 0 V (v Li / Li+), which indicates a decrease in the thermodynamic enthalpy of formation, can be observed in this case, and the pore size can preferably be measured by nitrogen physisorption.
[0019] The carbon layer may additionally contain a second type of pore and / or cavity accessible to the electrolyte. Since the second type of pore provides a large contact area with the electrolyte, alkali metal ions can effectively move from the electrolyte to the carbon layer and back, thereby achieving high charge-discharge currents with excellent reversibility (cycle stability). Importantly herein, since the electrolyte can penetrate deep into the carbon layer through the second type of pore, the deposition of metallic alkali metals can also occur in a specific manner through deeper layers of the anode's carbon layer, namely, through a deep "three-dimensional" interface having an enlarged surface compared to a shallow "two-dimensional" interface. The first type of pores also serve as "free space" for absorbing the metallic alkali metals deposited in the deeper layers of the carbon layer, because these pores are not filled with the electrolyte. As a result of the deposition of metallic alkali metals over a large surface and in the free space not filled with the electrolyte, the mechanical stress applied to the components of the secondary battery during operation of the secondary battery is significantly reduced. Accordingly, the alkali metal secondary battery according to the present invention has higher long-term stability and operational reliability than known alkali metal secondary batteries.
[0020] Compared to a shallow "two-dimensional" interface, a "three-dimensional" interface advantageously provides a contact surface to the electrolyte that is 2 to < 100 times larger than the "two-dimensional" contact surface to the electrolyte, preferably 3 to 30 times larger, preferably 5 to 20 times larger, particularly 8 to 12 times larger. For example, a higher "three-dimensional" contact surface in the range of 100 to 1000 times larger is ultimately disadvantageous because losses due to secondary reactions also occur at the interface between the carbon layer and the electrolyte, and these losses become disadvantageous when the contact surface is too large.
[0021] The pores and / or cavities of the second type may have spatial ranges in all three spatial directions within the micrometer range, particularly in the range of 1 μm to 1000 μm, and the spatial ranges can preferably be determined using an electron microscope.
[0022] In a preferred embodiment, the second type of pore and / or cavity preferably contains an electrolyte in the entire volume of the spatial range.
[0023] In the charged state, the carbon layer may contain an alkali metal, preferably lithium or sodium, and the alkali metal is preferably present in a ratio of 10 to 90 weight percent based on the total weight of the carbon layer.
[0024] In addition, when uncharged, the carbon layer may not contain any lithium or sodium, preferably alkali metals.
[0025] In a preferred embodiment, the electrolyte is a sulfidic solid electrolyte.
[0026] However, the electrolyte may also be a liquid electrolyte or a gel electrolyte, and all components of the electrolyte, in particular all molecules of the electrolyte, exceed the pore size of the first type and / or the pore size of the protective layer arranged between the electrolyte and the porous carbon particles, and the protective layer is conductive to alkali metal ions. The electrolyte preferably comprises or is composed of an ionic liquid.
[0027] In a preferred embodiment, the carbon layer forms a carbon network suitable for transporting alkali metal ions along the carbon network. This means that, in particular, the first type of pore is suitable for transporting alkali metal ions within the first type of pore (e.g., along the pore walls). When the alkali metal secondary battery is discharged, a certain distance inevitably exists between the alkali metal deposited in the pores and the electrolyte, which can be several hundred nm depending on the pore size. For complete discharge, complete return transport of the alkali metal stored in the pores is required, as well as complete return transport after oxidation of the alkali metal ions stored in the electrolyte. Such complete return transport can occur only when the carbon network, particularly the first type of pore, is suitable for guiding alkali metal ions into the electrolyte. It is desirable for the first type of pore to have these characteristics because it increases the discharge capacity of the secondary battery.
[0028] Type 1 pores in the carbon layer are together ≥ 0.5 cm 3 / g carbon, preferably ≥ 0.8 cm 3 / g carbon, particularly preferably ≥ 1.0 cm 3It can have a pore volume of 1 / g carbon. A high pore volume offers the advantage of providing a large space for absorbing metallic alkali metals generated by deposition, which provides high capacity and ensures high charge / discharge currents by maximizing the contact area with the electrolyte. Furthermore, a large pore volume means that the weight of the secondary battery can be kept low, which is a decisive advantage, particularly for mobile applications (low weight-to-power ratio).
[0029] The carbon layer may include micropores, mesopores, and / or macropores classified according to IUPAC, and preferably may include micropores classified according to IUPAC.
[0030] The carbon layer may be suitable for absorbing metallic alkali metals produced by electrochemical deposition in an amount such that it has a specific capacity of ≥ 400 mAh / g, preferably ≥ 600 mAh / g, particularly preferably ≥ 800 mAh / g, and particularly ≥ 1000 mAh / g based on the mass of the carbon material.
[0031] The electrolyte is at least 10 -10 S·cm -1 , preferably at least 10 -8 S·cm -1 , particularly preferably at least 10 -6 S·cm -1 , very particularly preferably at least 10 -4 S·cm -1 , especially at least 10 -3 S·cm -1 It has an ionic conductivity σ.
[0032] In a preferred embodiment, the electrolyte has lower conductivity for electrons than the electrically conductive substrate, or the carbon layer of the anode and / or the cathode; preferably, it is essentially non-conductive to electrons.
[0033] The electrolyte can be designed as a foil.
[0034] In addition, the electrolyte may have a maximum extension from the anode to the cathode in the range of 1 μm to 100 μm, preferably 10 μm to 50 μm.
[0035] The cathode may include a current collector, and the current collector is preferably in the form of a layer, and the layer is particularly preferably in the form of a stretched layer, a layer having double-sided coating, a layer of fiber fabric, or a layer having a primer layer.
[0036] The cathode may not contain an alkali metal source or may contain an alkali metal source, and the alkali metal source may preferably be present in a ratio of 60 to 99 weight percent based on the total weight of the cathode.
[0037] In addition, the cathode may contain a solid electrolyte.
[0038] In addition, the cathode may contain an electrically conductive additive.
[0039] Separately, the cathode comprises at least partially fibrilated polytetrafluoroethylene, and at least partially fibrilated polytetrafluoroethylene is preferably present in a ratio of less than 1 weight percent based on the total weight of the cathode.
[0040] In a preferred embodiment, the cathode is composed of the aforementioned components.
[0041] Alkali metal secondary batteries can be lithium secondary batteries or sodium secondary batteries.
[0042] The present invention further proposes the use of an alkali metal secondary battery according to the invention as an energy source for means of transport, buildings and / or electronic devices, preferably selected from the group consisting of automobiles, aircraft, drones, trains and combinations thereof. Brief explanation of the drawing
[0043] The subject matter according to the present invention is intended to be explained in more detail with the help of the following drawings and examples, without being limited to the specific embodiments shown in this specification. FIGS. 1a through 1c schematically illustrate the process at the interface between the electrolyte (8) and the carbon particles (6) of the carbon layer of the cathode of an alkali metal secondary battery according to the present invention, which is a lithium secondary battery in this specification. In the charging process illustrated in FIG. 1a, lithium ions are transported from the cathode (not shown) through the electrolyte (8) to the first type of pores (7) of the carbon particles (6). There, the lithium ions absorb electrons flowing from the conductive layer of the anode (not shown) to the carbon particles (6) and are reduced to lithium metal (10) currently located within the first type of pores (7). During the discharging process illustrated in FIG. 1b, the metallic lithium (10) attracts electrons and is oxidized into lithium ions (i.e., the metallic lithium is dissolved), and the lithium ions can be absorbed by the electrolyte and transported to the cathode. The situation illustrated in FIG. 1c illustrates the surprising discovery that even lithium metal (10) dissolved in lithium ions far from the electrolyte (8) is still efficiently transported to the electrolyte (8) and from there to the cathode. Thus, efficient transport of lithium ions along the first type of pore (7) in the direction of the electrolyte (8) must be possible. FIGS. 2A and 2B schematically illustrate the structure of an alkali metal secondary battery according to the present invention. In FIG. 2A, the secondary battery is illustrated in an uncharged state, and in FIG. 2B, the secondary battery is illustrated in a charged state. The illustrated alkali metal secondary battery comprises a cathode (1) and an anode (2) comprising an electrically conductive substrate (3), wherein the electrically conductive substrate (3) extends over a specific geometric region (4) and a carbon layer (5) is arranged over at least a portion of this region (4), and the carbon layer (5) comprises carbon particles (6) having a first type of pore (7) and forming electrically conductive contacts with the electrically conductive substrate (3) of the anode (2). The secondary battery further comprises an electrolyte (8) arranged between the cathode (1) and the anode (2) and having alkali metal ion conductive contacts with the carbon particles (6) of the cathode (1) and the anode (2). The carbon layer (5) has a second type of pore (9) between the carbon particles (6), which contains an electrolyte (8) in at least the area, and the first type of pore (7) has a small pore size that is unsuitable for absorbing the electrolyte and suitable for absorbing the metallic alkali metal (10) produced by deposition. In FIG. 10, the deposition of the metallic alkali metal (10) is shown in a simplified form only in a few of the first type of pores (7). FIG. 3 shows the experimental results performed with an alkali metal secondary battery (lithium secondary battery) according to the present invention. The voltage profile for lithiation is indicated by a dashed line, and the voltage profile for delithiation is indicated by a solid line. The lithium secondary battery was a half-cell having an anode, a lithium metal foil as a cathode, and a sulfide solid electrolyte as described in claim 1. Lithiation or delithiation was 0.05 mA / cm² 2 It occurred at a constant current. The specific capacity for delithiation was determined to be 423 mAh / g. Figure 4 illustrates the potential profiles of the results of the third and fourth cycles of lithiation and delithiation for the TiC-CDC cell in the example. The reversible lithiation capacity of 521.0 mAh / g TiC-CDC could be observed in the third cycle of the half cell. Specific details for implementing the invention
[0044] Example - Capacity of an alkali metal secondary battery according to the present invention
[0045] All material processing was performed in an inert gas.
[0046] First, the carbon material TiC-CDC was dried at 200°C for 12 hours under inert gas conditions. This carbon material has a first type of pore with a pore size of < 2 nm, and the pore size can be determined by nitrogen physisorption.
[0047] To produce a powdered composite electrode (anode), dried TiC-CDC was mixed with i) gas-phase grown carbon nanofibers (VG-CNF), ii) a conductive carbon additive, and iii) a solid electrolyte (Li6PS5Cl = SE) in a mass ratio of 60:5:35 in agate mortar for 30 minutes.
[0048] Next, a half cell was fabricated in a stainless steel outer casing with a Teflon liner using a die with a diameter of 13 mm. To do this, a Li foil (counter electrode) with a diameter of 13 mm and a thickness of 50 μm was placed on the die, and 150 g of solid electrolyte powder (Li6PS5Cl powder = SE powder) was uniformly distributed over it using a micro spatula. This composition was compressed and bound into pellets.
[0049] Then, the TiC-CDC composite powder (7.44 mg) (test electrode) was homogeneously distributed onto the bonded solid electrolyte surface of the die and re-bonded using a 4-ton hydraulic press for 30 seconds. The active material stress of the resulting cell was 3.36 mg / cm² 2 was.
[0050] The electrochemical behavior of the cell was measured using a battery tester VMP3 (BioLogic, France). In this specification, the reversible capacity of the anode (having a carbon layer according to the present invention) at a constant temperature of 25°C was tested against a counter electrode (lithium metal foil) at a potential greater than 0 V and at a potential of 0 V (vs. Li / Li+).
[0051] Various cycles were performed in subsequent steps at a constant voltage from 0 V until the current exceeded -0.01 mA, involving lithiation of the carbon-active material of the carbon layer to 0 V and delithiation of the carbon-active material of the carbon layer to 2 V. The applied current was 0.065 mA.
[0052] The generated potential profiles of the third and fourth cycles of lithiation and delithiation for the TiC-CDC cell are shown in Fig. 4. The reversible lithiation capacity of 521.0 mAh / g TiC-CDC could be observed in the third cycle of the half cell.
[0053] List of reference symbols
[0054] 1: Cathode;
[0055] 2: Anode;
[0056] 3: Electrically conductive substrate of the anode;
[0057] 4: Extension to a specific geometric region;
[0058] 5: Carbon layer;
[0059] 6: Carbon particles;
[0060] 7: Type 1 pores of the carbon layer;
[0061] 8: Electrolytes;
[0062] 9: Type 2 pores of the carbon layer;
[0063] 10: A metallic alkali metal (e.g., lithium) produced by deposition in a Type 1 pore.
Claims
Claim 1 As an alkali metal secondary battery, a) a cathode; b) an anode comprising or composed of a carbon layer, wherein the carbon layer forms an electrically conductive contact alone or in combination with an electrically conductive substrate; and c) an electrolyte arranged between a cathode and an anode and having alkali metal ion conductive contacts on the carbon layers of the cathode and anode; said carbon layer comprises a first type of pore that is inaccessible to the electrolyte and absorbs an alkali metal electrochemically deposited in metallic form during the charging process of the alkali metal secondary battery, said first type of pore having a pore size in the range of 0.5 to 100 nm, said pore size can be determined by nitrogen physisorption, said carbon layer further comprises at least one of a second type of pore and a cavity accessible to the electrolyte, said second type of pore and said cavity having a spatial range in all three spatial directions in the range of 1 μm to 1000 μm, said spatial range can be determined by electron microscopy, said electrolyte is a sulfide solid electrolyte, and said first type of pores in the carbon layer together ≥ 0.5 cm 3 It has a pore volume of carbon / g, and the sulfide solid electrolyte is at least 10 -3 S·cm - Alkali metal secondary battery having an ionic conductivity σ. Claim 2 An alkali metal secondary battery according to claim 1, wherein the first type of pore is provided with a chemical modification favorable for the absorption of a metallic alkali metal generated by deposition, said chemical modification is selected from the group consisting of a layer on the pore surface, nanoparticles on the pore surface, at least one chemical functional group on the pore surface, and combinations thereof. Claim 3 An alkali metal secondary battery according to claim 1, characterized in that at least one of the second type of pore and the cavity comprises an electrolyte. Claim 4 In paragraph 3, an alkali metal secondary battery wherein at least one of the second type of pores and the cavity comprises an electrolyte in the entire volume of the spatial range. Claim 5 An alkali metal secondary battery according to claim 1, wherein the carbon layer does not contain lithium or sodium when uncharged. Claim 6 An alkali metal secondary battery according to claim 1, characterized in that the carbon layer forms a carbon network that transports alkali metal ions along the carbon network. Claim 7 An alkali metal secondary battery according to claim 1, wherein the carbon layer comprises micropores classified according to IUPAC. Claim 8 An alkali metal secondary battery according to claim 1, wherein the carbon layer absorbs a metallic alkali metal produced by electrochemical deposition in an amount such that it has a specific capacity of ≥ 400 mAh / g based on the mass of the carbon material. Claim 9 An alkali metal secondary battery according to claim 1, wherein the electrolyte has a maximum extension in the range of 1 μm to 100 μm from the anode in the cathode direction. Claim 10 An alkali metal secondary battery according to claim 1, wherein the cathode comprises at least partially fibrinous polytetrafluoroethylene, and the fibrinous polytetrafluoroethylene is present in a ratio of less than 1 weight percent based on the total weight of the cathode. Claim 11 An alkali metal secondary battery according to claim 1, characterized in that the alkali metal secondary battery is a lithium secondary battery or a sodium secondary battery. Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete Claim 16 delete Claim 17 delete
Citation Information
Patent Citations
An anode for all-solid type batteries including solid electrolyte
KR1020190044397A
Graphene-Metal Hybrid Foam-Based Electrode for an Alkali Metal Battery
US20170352869A1
